2011
DOI: 10.1177/1073191111401172
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Interpersonal Circumplex Model in Late Childhood

Abstract: The authors developed the Interpersonal Behavior Questionnaire for Children with the aim of assessing the constructs of the interpersonal circumplex model, that is, Dominance and Love and their possible combinations, via third- to fifth-grade children's self- and peer reports. In the three studies presented herein, the authors examined several psychometric properties of the questionnaire. Results demonstrated that children's ratings along the questionnaire yielded the hypothesized circumplex structure of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…Thus, our findings suggest that as child ADHD symptoms increase, both dyad members are less likely to respond to their partners' affiliative behaviour with an affiliative gesture. Such findings extend previous work on the interpersonal behaviours of children (e.g., Di Blas, 2007;Di Blas, Grassi, Luccio, & Momentè, 2012;Markey et al, 2005;Pennings et al, 2014;Sodano & Tracey, 2006;Thijs, Koomen, Roorda, & ten Hagen, 2011), and show that during interactions, children influence and are influenced by the interpersonal behaviours of their mothers. Past work has examined how a child's behaviour profile impacts complementarity.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our findings suggest that as child ADHD symptoms increase, both dyad members are less likely to respond to their partners' affiliative behaviour with an affiliative gesture. Such findings extend previous work on the interpersonal behaviours of children (e.g., Di Blas, 2007;Di Blas, Grassi, Luccio, & Momentè, 2012;Markey et al, 2005;Pennings et al, 2014;Sodano & Tracey, 2006;Thijs, Koomen, Roorda, & ten Hagen, 2011), and show that during interactions, children influence and are influenced by the interpersonal behaviours of their mothers. Past work has examined how a child's behaviour profile impacts complementarity.…”
Section: Discussionsupporting
confidence: 89%
“…This implies that the general theoretical assumptions of the two-factor structure are applicable, but the octants of the IPC cannot be adequately represented by the IMI@YA. Former studies on IPC in children (di Blas, 2007;di Blas et al, 2012) or parent-child dyads (Markey et al, 2005) confirmed the expected circular structure of the IPC in self-ratings of actual behavior. This suggests that the interpersonal behaviors of parents and children follow the structure of the model, whereas interpersonal perceptions and covert reactions are only roughly aligned with the two basic dimensions (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…Circumplex models are common in different lines of psychological research. For instance, they are discussed as appropriate models of relations among affective states (Fabrigar et al, 1997;Gurtman & Pincus, 2000;Gurtman & Pincus, 2003;Remmington et al, 2000;Tracey, 2000) and interpersonal problems (Alden et al, 1990;Boudreaux et al, 2018;Di Blas et al, 2012;Hopwood et al, 2011;Hopwood & Good, 2019;Locke, 2000;Zimmermann & Wright, 2017).…”
Section: Study 2 Motivationmentioning
confidence: 99%
“…One reason for this is that circumplex models are not necessarily entertained through FA (Browne, 1992). Another reason is that even when circumplex models are estimated through EFA or PCA, none of the formal methods to determine the number of factors are commonly applied (Alden et al, 1990;Boudreaux et al, 2018;Di Blas et al, 2012;Hopwood et al, 2011;Hopwood & Good, 2019;Locke, 2000). Still, circumplex models suffice our intention to review NEST and EGA in light of cross-loadings as they have a clearly defined number of factors.…”
Section: Study 2 Motivationmentioning
confidence: 99%
See 1 more Smart Citation